Endostatin, an Inhibitor of Angiogenesis, Decreases After Bidirectional Superior Cavopulmonary Anastamosis - Field-Ridley, Aida; Heljasvaara, Ritva; Pihlajaniemi, Taina; Adatia, Ian; Sun, Christine; Keller, Roberta L.; Gong, Wen Hui; Datar, Sanjeev; Oishi, Peter; Fineman, Jeffrey R. (Pediatric cardiology, 2013)
Pulmonary arteriovenous malformations (PAVMs) are a common source of morbidity after bidirectional superior cavopulmonary anastomosis (Glenn). The diversion of hepatic venous effluent away from the pulmonary circulation after Glenn appears to play a significant role in the pathogenesis of PAVMs. Although the liver is known to produce factors that regulate vascular development, specific hepatic inhibitors of angiogenesis have not been described in the post-Glenn population. Endostatin, produced from its precursor collagen XVIII, is a potent inhibitor of angiogenesis produced by the liver. This study aimed to investigate the hypothesis that endostatin levels decrease in patients after Glenn. Levels of endostatin and its precursor, long-type collagen XVIII, were determined by enzyme-linked immunoassay and immunoprecipitation, respectively, for serum samples from 38 patients undergoing Glenn, total cavopulmonary anastomosis (Fontan), or biventricular repair of cardiac defects. Samples were obtained before surgery and 24 h afterward. In patients undergoing a bidirectional Glenn procedure, endostatin levels decreased after surgery ( n = 17; 4.42 vs 3.34 ng/ml; p < 0.001), and long type-collagen XVIII levels increased by 200 % ( n = 10; p = 0.0001). However, endostatin levels did not change after surgery in patients undergoing Fontan ( n = 13) or biventricular repair ( n = 8). In patients undergoing Fontan, long-type collagen XVIII increased by 18 % ( p < 0.01), whereas in control subjects, the levels were unchanged. These data suggest that the diversion of hepatic blood flow away from the pulmonary circulation in patients after the Glenn procedure inhibits endostatin production from collagen XVIII, resulting in decreased circulating serum endostatin levels. A decrease in endostatin may promote angiogenesis. The mechanism whereby the pulmonary circulation processes endostatin and its potential role in the pathogenesis of PAVMs warrant further study.